THE LITERACY AND NUMERACY ABILITY PROFILE WHICH ARE VIEWED FROM MINIMUM ASSESSMENT COMPONENTS (AKM) - Mellyzar, Mellyzar; Novita, Nanda; Muliani, Muliani; Marhami, Marhami; Retnowulan, Sri Rahayu (UIN AR-RANIRY, 2023)
Literacy and numeracy skills are cognitive learning outcomes measured in the Minimum Competency Assessment (AKM) and are part of the National Assessment (AN). This study aims to describe the literacy and numeracy achievement profile of junior high school students in terms of three aspects, namely content, cognitive processes, and context The descriptive quantitative approach method used in this research involved 141 class VIII junior high school students in North Aceh Regency and Lhokseumawe City through random sampling. Respondents are participants who took part in the 2021 National Assessment. The research instrument used was a question on literacy with 26 questions and numeracy with as many as 30 questions according to the grid and aspects of the AN that had been validated. The context of the questions is arranged in the form of personal, socio-cultural, and scientific. The distribution of the questions is in the form of 20% multiple-choice, 60% complex multiple-choice, 10% matching, 5% short answer or short answer, and 5% description. The results showedthe average percentage score of literacy ability was 43.87% with low criteria, meanwhile for numeracy skills, the average percentage score was 33.91% with very low criteria. These results indicate that students' literacy and numeracy skills in terms of each content need to be improved through the implementation of learning programs and the use of textbooks that lead to the improvement and development of literacy and numeracy skills.